Scattering Mechanisms from Roughness-induced Fluctuations in Charge Distributions in ZnO Surface Quantum Wells - Tuan, Le; Tien, Nguyen Thanh; An, Tran Thi; Quang, Doan Nhat (Communications in Physics, 2012)
We present a theoretical study of roughness-related scattering mechanisms for electrons in single heterostructures, especilaly in Gaussian-doped ZnO surface quantum wells. We show that besides the conventional scatterings there must exist roughness-related mechanisms of charge origin, which stem from fluctuations the electron density and the donor density in the bulk ZnO. The strength of the two charge-origin scattering sources is found to be comparable with the one of the standard one from fluctuations in the barrier position. The effect of the dielectric discontinuity on the scattering mechanisms is discussed